2009
DOI: 10.1128/jb.00597-08
|View full text |Cite
|
Sign up to set email alerts
|

Retentive Memory of Bacteria: Long-Term Regulation of Dehalorespiration in Sulfurospirillum multivorans

Abstract: The gram-negative, strictly anaerobic epsilonproteobacterium Sulfurospirillum multivorans is able to gain energy from dehalorespiration with tetrachloroethene (perchloroethylene [PCE]) as a terminal electron acceptor. The organism can also utilize fumarate as an electron acceptor. Prolonged subcultivation of S. multivorans in the absence of PCE with pyruvate as an electron donor and fumarate as an electron acceptor resulted in a decrease of PCE dehalogenase (PceA) activity. Concomitantly, the pceA transcript l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 24 publications
4
43
0
Order By: Relevance
“…Different adaptation processes for the same outcome. By following the experimental approach employed previously by John and coworkers for Sulfurospirillum multivorans (8), our study highlights a completely different mechanism by which D. hafniense strain TCE1 stopped the production of PceA in the prolonged absence of its substrate, PCE. The direct genetic environments of the pce gene cluster in strain TCE1 already suggested that pceA was strongly and constitutively expressed by the promoter embedded in the vicinal insertion sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different adaptation processes for the same outcome. By following the experimental approach employed previously by John and coworkers for Sulfurospirillum multivorans (8), our study highlights a completely different mechanism by which D. hafniense strain TCE1 stopped the production of PceA in the prolonged absence of its substrate, PCE. The direct genetic environments of the pce gene cluster in strain TCE1 already suggested that pceA was strongly and constitutively expressed by the promoter embedded in the vicinal insertion sequence.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we used an approach inspired by a recent study on the reductive dehalogenase of Sulfurospirillum multivorans (8). Starting from a culture routinely cultivated on PCE, we transferred strain TCE1 into a medium containing fumarate and successively transferred the culture 30 times in the absence of PCE.…”
mentioning
confidence: 99%
“…Whether Dcmb_86 has a role in the dechlorination of PCE to TCE can only be determined by biochemical studies. So far it cannot be ruled out that unknown long-term regulatory effects keep its formation at a high level over consecutive transfers in the absence of the inducing compound, as has been reported for PceA in Sulfurospirillum multivorans (52). Two further Rdh proteins, Dcmb_ 1341 and Dcmb_1444, were indicated in the proteomes of the first and second transfer with PCE; however, the expression seems less substrate specific, because they were also detected in at least some replicates of 1,2,3-TCB-grown cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE, 12.5%) was used to separate proteins of S. blattae crude extracts (10 g protein/lane). The immunoblot was generated as described by John et al (32). The Strep-tag-specific antibody solution (IBA, Göttingen, Germany) was diluted 3,000-fold, and the antibodies were detected via a secondary antibody coupled to alkaline phosphatase (Sigma-Aldrich, Munich, Germany).…”
Section: Methodsmentioning
confidence: 99%